منهج عبد الرحمن السميط في الدعوة في قارة إفريقيا : دراسة تحليلية - غريب، مبارك فيصل مبارك (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research discusses 'Abd al-Raḥman Sumayṭ's method of preaching and its impact on the African continent. It starts by highlighting his biographical and intellectual backgrounds and afterwards focuses on his charitable projects and intellectual contributions in the field of da'wah. The impact of these two aspects in the success of his preaching has also been highlighted. His various achievements such as building of the mosques, establishment of universities and so on have been elaborated. In addition, the methods and means which he used in his preaching and the characteristics of his methodology have also been pointed out. This research has adopted inductive and analytical approaches. By using them the study traces and explores his tremendous achievements through written, audio and video materials that document the history of his preaching. The study analyses them to understand his approach, methods and means which led to the conversion of more than 11 million people to Islam. The main aim here is to introduce his method to various preachers so that they can benefit from and apply it in their preaching. The research ends by pointing out some findings; the most important of them is the discovery of Sumayṭ's elevated morals and their great effect on the success of his preaching. Finally, the researcher presents some recommendationsespecially the need to deduce some qualities of da'wah which have been extant in his person and benefit from them in the field of da'wah.